HEALTHCARE HORIZONS: INNOVATIONS AND INTERDISCIPLINARY APPROACHES IN NURSING AND HEALTH ASSISTANCE - Mohammed Kalif Aldafery, Salmaa Kalif Aldafery, Fawaz Brik AlJumaili, Awadh Hamoud Hamed Almutairi,; Abd Al Hadi Selman Agll Alshmriy, Fahad Ghayib Awad Alshammari, Falah Aftan Khalif Aldhafeeri, Ahmed lafi aldhafeeri, (Chelonian Research Foundation, 2022)
The healthcare landscape is rapidly evolving, with a growing emphasis on interprofessional collaboration and innovation. This study aimed to investigate the relationship between interprofessional communication and job satisfaction among nutrition and epidemiology technicians in Saudi Arabia. A cross-sectional survey was conducted among 543 technicians using the Interprofessional Collaboration Scale (ICS) and the Job Satisfaction Survey (JSS). Quantitative data analysis revealed moderate to high levels of interprofessional communication and job satisfaction, with significant differences based on healthcare role and work setting. Qualitative findings highlighted the benefits, barriers, and strategies for improving interprofessional communication and job satisfaction. The study emphasizes the importance of fostering a culture of collaboration and providing support for healthcare professionals to enhance job satisfaction and patient outcomes. The findings have implications for healthcare organizations, policymakers, and educators in Saudi Arabia and beyond. Keywords: interprofessional communication, job satisfaction, nutrition technicians, epidemiology technicians, Saudi Arabia